Treatment of Ankyloglosia with Coblation Assisted Surgery - Caner Sahin (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Ankyloglossia is a disease characterized by difficulty in breast-feeding, limitation of tongue, andspeech disorders. Prevalence of the disease is %1-10 in the literature (1). Cold knife, Laser surgery,electro cautery methods are used in the surgical treatment of the disease. Coblation radiofrequency technology provides low temperature work with minimal damage to neighborhood tissues. We presenta 21 years old male with ankyloglossia treated by coblation surgery in the lights of the literature.